Large-scale land-suitability mapping in the GIS environment for the construction site of the University Olympic Village in Izmir (Turkey) - Kincal, Cem; Koca, M. Yalçin; van Loon, A.J. (Tom) (Geologos, 2009)
Participants of the 23rd University Olympic Games held in Izmir (Turkey) were hosted in a Universiade Olympic Village that had to be newly constructed. A risk analysis has been performed to assess potential engineering problems at the envisaged construction site. The risk analysis was largely based on a new, large-scale land-suitability map that was prepared in the GIS environment with much detail for this type of construction work. Information was collected from several maps, in combination with mapping in the ﬁeld, drilling and seismic data. Geological, geotechnical, geophysical and morphological data were then superimposed on these analyses. This sequence of overlay analyses was performed with the help of GIS software (MapInfo Professional 7.5); this resulted in ﬁve hazard maps. Risk points (1–11) were then attributed to the different zones in the ﬁve digital hazard maps. A land-suitability map indicating the suitability for envisaged constructional activities was subsequently obtained in the form of an overlay of the ﬁve hazard maps, thus allowing to calculate a total risk for each zone on this map. The land-suitability map that was thus obtained, has been prepared for a 1:1,000 scale development plan; such a large scale is uncommon in this context.